The Name ‘Palestine’ in Classical Greek Texts - Alonso Serrano, Carmelo A. (Journal of Holy Land and Palestine Studies, 2021)
This article provides a contextualised exposition of classical Greek texts, in chronological order, from Herodotus to Eusebius of Caesarea (5th century BC-4th century AD), with brief biographical reviews and in which the name ‘Palestine’ appears. A Latin text by Pomponius Mela is also included for its reference to Gaza which, with the exception of the Septuagint texts, predates Arrian, Arrian of Nicomedia, a Greek historian of the Roman period, by nearly a century. The selection of classical texts explored in this article is not intended to be exhaustive; however, the exploration of these texts in connection with Palestine has never been attempted before. While avoiding historical, philosophical or literary criticism of these texts, this article focuses on the specific considerations of the name ‘Palestine’ in the classical literature.